Peran dan implementasi kegiatan laboratorium tradisional dan inquiry dalam penguatan keterampilan abad 21 pada pembelajaran sains - Lesmana, Elkis Tri; Malik, Adam (Papanda Journal of Mathematics and Science Research, 2025)
Laboratory activities play a crucial role in science education, especially in enhancing critical thinking, problem-solving, and creativity, which are essential 21st-century skills. This article examines the essence, competency values, the development of practicum models, and recent research findings on the use of traditional (cookbook/verification) and inquiry laboratories in science education. The study uses 40 recent references, including international and national journals published between 2020-2024 and dissertations. The findings indicate that inquiry-based practicum activities are more effective in fostering higher-order thinking skills compared to traditional models.